Women's motivations for sex: Exploring the diagnostic and statistical manual, fourth edition, text revision criteria for hypoactive sexual desire and female sexual arousal disorders - Carvalheira, Ana Alexandra (2013)
Introduction. There are problems with the existing definition of hypoactive sexual desire disorder (HSDD) in that desire for sex and sexual fantasy are not a universal experience. Aims. To explore: (i) women’s motivations to engage in sexual activity; (ii) frequency and predictors of sexual fantasies; (iii) sexual arousal; (iv) recognition of sexual arousal; and (v) association between relationship duration and these variables. Methods. Three thousand six hundred eighty-seven women completed a web-based survey of previously pilot-tested items. Main Outcome Measures. Investigator-derived self-report questions of sexual desire and arousal, and sexual fantasies. Results. Among women who easily became aroused, 15.5% reported only engaging in sex if they felt sexual desire at the outset whereas 30.7% typically or always accessed desire only once they were aroused. Women in longer-term relationships engaged in sex with no sexual desire more often (42%) than women in short-term relationships (22.4%) (P < 0.001). The percentage of women that reported fantasies only sometimes was 52.5%. A logistic regression revealed that religion (odds ratio [OR] = 1.45; P < 0.001), difficulty getting aroused (OR = 0.511; P < 0.001), responsive desire (OR = 0.919; P < 0.05), and frequency of orgasm (OR = 1.11; P < 0.05) were significantly associated with sexual fantasy. After controlling for age, relationship duration was negatively associated with frequency of initiating sex (r = -0.116, P < 0.001), women’s satisfaction with their own sexuality (r = -0.173, P < 0.001) and sexual satisfaction with the partner (r = -0.162, P < 0.001). Conclusions. Results reflect diversity in women’s motivations for sex, and there is evidence that responsive desire occurs in women with and without arousal difficulties. We strongly recommend relationship duration as well as adequacy of partner sexual stimulation to be recognized in any future diagnostic framework of dysfunction. Clinical implications as well as those for future diagnostic nomenclature are considered.